Predicting Indonesian Movie Choice: Integrating Sor For Trailers and ELM For Digital Communications - Siwi Hershita Danti; Anna Amalyah Agus (Eduvest - Journal of Universal Studies, 2025)
This study aims to analyze the influence of film trailer attributes and digital marketing communication on the intention to watch movies in cinemas in Indonesia, by considering the role of attention mediation and attitude/elaboration based on the theoretical approach of Stimulus-Organism-Response (SOR) and Elaboration Likelihood Model (ELM). The research method used a quantitative approach with an online survey of 284 respondents who were used to watching movies in cinemas. The results showed that third-party designations (such as reviews and recommendations) significantly affected the audience's attention and attitudes/elaborations, while the film's official social media activity had no significant effect on attitudes. The trailer attributes have also been shown to have a positive effect on attitudes/elaboration. Attitude/elaboration is the strongest predictor of ticket purchase intention. These findings effectively integrate SOR and ELM theories, confirming the importance of peripheral paths through third parties and trailer quality in film marketing strategies.